781 Validation of the combinatorial effect of blinatumomab and nivolumab in cancer therapy. (10th December 2020) - Wang, Tienan; Lin, Qing; Zhang, Jie
Abstract : Background: Cancer immunotherapies, including immune checkpoint inhibitors, CAR-T, cancer vaccines and bispecific antibodies, have been brought to spot light in recent years as several therapeutic strategies targeting the immune system have produced exciting clinical results. Bispecific antibody typically play dual roles in blocking the immune checkpoint and redirecting/re-boosting the function of the immune effector cells. Blinatumomab belongs to CD3 bispecific T cell engager (CD3 BiTE), which was engineered to harbor two arms binding with CD3 and CD19 simultaneously and direct CD8+ T cells to specifically recognize CD19 positive lymphoma cells to execute cytotoxicity. Approval of Blinatumomab for patients with relapse/refractory B cell acute lymphoblastic leukemia (ALL) has driven remarkable increase in combination studies of Blinatumomab with other immunotherapies such as checkpoint inhibitors. Methods: In this study, we developed CD8+ T cytotoxic system targeting different B lymphoma cell line and fully validated the function of Blinatumomab in promoting target tumor cell lysis by primary CD8+ T cells (figure 1 ). In addition, we established a mixed lymphocyte and tumor system to mimic physiological TME to dissect the combinational role of Nivolumab and Blinatumomab (figure 2 ). Results: The result suggest that combinatory therapy is highly depend on the dosage of Blinatumomab and also T cell number in the TME, which might give an instruction for ongoing clinical trial design. Finally, we have employed humanized mouse models bearing Raji or Daudi tumor cells to further validate this combination treatment in vivo. Both In-vivo and In-vitro data support that Blinatumomab is dominant in activing T cell and Nivolumab can only exhibit synergistic effect under suboptimal dosage of Blinatumomab. Conclusions: Successfully establish in vitro system to evaluate the function of CD3 BiTE and also take advantage of MLR/tumor co-culture system to demonstrate PD1 antibody could further promote T cell activation under appropriate dosage of CD3 BiTE.